2012
DOI: 10.2478/v10006-012-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Computer methods for stability analysis of the Roesser type model of 2D continuous-discrete linear systems

Abstract: Asymptotic stability of models of 2D continuous-discrete linear systems is considered. Computer methods for investigation of the asymptotic stability of the Roesser type model are given. The methods require computation of eigenvalue-loci of complex matrices or evaluation of complex functions. The effectiveness of the stability tests is demonstrated on numerical examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The main purpose of this paper is to present new computational methods for checking the condition (6) of asymptotic stability of the model (1) which do not require a priori knowledge of the characteristic bivariate polynomial (5).…”
Section: Problem Formula Onmentioning
confidence: 99%
See 1 more Smart Citation
“…The main purpose of this paper is to present new computational methods for checking the condition (6) of asymptotic stability of the model (1) which do not require a priori knowledge of the characteristic bivariate polynomial (5).…”
Section: Problem Formula Onmentioning
confidence: 99%
“…It is easy to see that conditions (9) and (10) can be written in the forms (7) and (8), respectively. Lemma 1.…”
Section: Solu On Of the Problemmentioning
confidence: 99%
“…Secondly, compared with continuous-time models, the advantage they offer is that they are generally more direct, more convenient and more accurate to formulate. Thirdly, recent works have shown that for discrete-time models the dynamics can produce a much richer set of patterns than those observed in continuous-time models (Busłowicz, 2010;Busłowicz and Ruszewski, 2012;Duda, 2012;Feedman, 1980;Holling, 1965;Huang and Xiao, 2004;Hsu, 1978;Raja et al, 2011;Xu et al, 2011;Zhang et al, 2011). At last, we can get more interesting dynamical behaviors and more accurate numerical simulations results from the discrete-time models; moreover, numerical simulations of continuous-time models are obtained by discretizing the models.…”
Section: Introductionmentioning
confidence: 99%
“…There are fruitful achievements on this item in the past decades. To list some of these, Buslowicz (2010aBuslowicz ( , 2010b, Kaczorek (2011aKaczorek ( , 2011b discussed the stability and robust stability of positive 2-D continuous-discrete systems in general model, and Buslowicz and Ruszewski (2012) gave the computer methods for stability analysis of the Roesser type model of 2-D continuousdiscrete linear systems. Xiao in (2001aXiao in ( , 2001bXiao in ( , 2001cXiao in ( , 2003 investigated the stability and robust stability test for 2-D continuous-discrete linear systems in Roesser model, FM model and recursion model, respectively.…”
Section: Introductionmentioning
confidence: 99%